Synthesis and characterization of reduced grahene oxide (rGO) / tips-pentacene composite material for organic thin film transistor (OTFT) sensor platform - Nurhazwani Musa (School of Material Engineering, 2016)
The main objective of this research was to prepare a composite material for OTFT sensor platform in order to improve performance of the material when compared to the pure organic material and reduced graphene oxide (rGO). This main objective was accomplished by the following specific objectives, to synthesis, characterize and optimize the performance of grapheme oxide (GO) and reduced graphene oxide (rGO), to fabricate and evaluate the performance of OTFT using different parameters and to optimize the performance of rGO/TIPS-Pentacene composite for improved device performance using different solvents.